Biogeochemical properties of eddies in the California Current System. Issue 11 (11th June 2016) - Chenillat, Fanny; Franks, Peter J. S.; Combes, Vincent
Abstract: The California Current System (CCS) has intense mesoscale activity that modulates and exports biological production from the coastal upwelling system. To characterize and quantify the ability of mesoscale eddies to affect the local and regional planktonic ecosystem of the CCS, we analyzed a 10 year‐long physical‐biological model simulation, using eddy detection and tracking to isolate the dynamics of cyclonic and anticyclonic eddies. As they propagate westward across the shelf, cyclonic eddies efficiently transport coastal planktonic organisms and maintain locally elevated production for up to 1 year (800 km offshore). Anticyclonic eddies, on the other hand, have a limited impact on local production over their ~6 month lifetime as they propagate 400 km offshore. At any given time ~8% of the model domain was covered by eddy cores. Though the eddies cover a small area, they explain ~50 and 20% of the transport of nitrate and plankton, respectively. Key Points: Eddies in coastal upwelling systems contribute to export of coastal production Cyclonic and anticyclonic eddies have asymmetric roles in controlling biology Cyclonic eddies play a major role in redistributing and enhancing biology